2016
DOI: 10.1371/journal.pone.0145425
|View full text |Cite|
|
Sign up to set email alerts
|

SIRT1 Activity Is Linked to Its Brain Region-Specific Phosphorylation and Is Impaired in Huntington’s Disease Mice

Abstract: Huntington’s disease (HD) is a neurodegenerative disorder for which there are no disease-modifying treatments. SIRT1 is a NAD+-dependent protein deacetylase that is implicated in maintaining neuronal health during development, differentiation and ageing. Previous studies suggested that the modulation of SIRT1 activity is neuroprotective in HD mouse models, however, the mechanisms controlling SIRT1 activity are unknown. We have identified a striatum-specific phosphorylation-dependent regulatory mechanism of SIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 50 publications
0
33
3
Order By: Relevance
“…SIRT1 is a member of the Sirtuin protein family, which is associated with cell stress reaction regulation, DNA repair, chromatin recombination, metabolism, aging and apoptosis due to the acetyl enzyme function of co-enzyme NAD + to SIRT1 ( 23 , 24 ). The function of SIRT1 in cancer is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is a member of the Sirtuin protein family, which is associated with cell stress reaction regulation, DNA repair, chromatin recombination, metabolism, aging and apoptosis due to the acetyl enzyme function of co-enzyme NAD + to SIRT1 ( 23 , 24 ). The function of SIRT1 in cancer is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, exogenous NAM could have beneficial effects, but this has yet to be reported. It has been noted that sirtuins, especially SIRT1, can directly influence brain function (Barhwal et al 2015;Fujitsuka et al 2016;Koltai et al 2011;Sarga et al 2013;Torma et al 2014;Tulino et al 2016). SIRT1 appears to be involved in neuronal stem cell differentiation (Ma et al 2014), synaptic plasticity (Michan et al 2010) and metabolism (Li et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the assessment of the presence of transgene on Sirt mRNA expression changes in key structures (striatum, overlying cortex, cerebellum) of the regulation of motor functions, our study design involved the determination of the effect of aging and its interaction with the presence of the transgene with a view on gender-related effects as well. First of all, we found no significant differences between genders regarding either of the above-mentioned aspects, and therefore gender issues seemingly did not introduce bias into the studies of Tulino et al and Reynolds et al [45,61]. Similarly to the study of Tulino et al [61], we found no effect of the transgene in the striatum regarding either age groups, but a marked increase in Sirt1 expression was demonstrated in cortical and cerebellar samples of tg animals compared to wt controls in all age groups similar to that found by Reynolds et al [45] applying whole brain samples.…”
Section: Discussionmentioning
confidence: 51%
“…Accordingly, we aimed at contributing to the clarification of the controversies regarding Sirt1 and Sirt3 mRNA expression patterns by a better characterization of region-and aging-specific changes in the mRNA expression levels of Sirt1 and three Sirt3 isoforms using the N171-82Q tg mouse model of HD. Tulino et al found a significant decrease in striatal Sirt1 mRNA expression from 4 to 9 weeks in the wt group, whereas cerebellar Sirt1 mRNA expression increased significantly by 9 and 14 weeks of age in the same control group in experiments with R6/2 mouse model of HD (MRN: 204) [61]. The presence of the transgene seemingly did not affect Sirt1 mRNA expression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation